2009 Rapid Excavation and Tunneling Conference Proceedings - Almeris, Gary (SME, 2009)
Included in this massive 1400 page volume are more than 100 papers presented at the 2009 Rapid Excavation and Tunneling Conference, the largest and msot prestigiuous assemblage of industry experts and practitioners in the world. In these pages, you can go underground for a gritty, up-close and personal look at dozens of case histories from around the globe. You will find no "sugarcoating" in these accounts. Along with the success stories, you'll benefit from candid discussions of problems and missteps and will learn how you can avoid similar mistakes in your own future projects.
Keywords: Tunneling -- Congresses.; Excavation -- Congresses.; elektronické knihy; electronic books